Reliability and criterion validity of the concept 2 SkiErg™ to assess 1,000-m on-snow, time trial performance—a case study - O'Brien, Brendan J.; Worn, Ryan; Clark, Brad; Spencer, Matt (Frontiers in Sports and Active Living, 2025)
ObjectivesThis study investigated the reliability and criterion validity of the Concept 2 SkiErg™ to assess 1,000-m on-snow, time trial performance using the classical double poling technique.MethodsTen athletes (5 males and females) from a National cross-country ski team participated in the study and completed a 1,000-m time trial on snow, as well as two 1,000-m time trials on the Concept 2 SkiErg™ in a temperature-controlled room during a 4-day training camp.ResultsThere was a significant decrease in time from test 1 to test 2 of 4.87 s [238.3 ± 26.1 vs. 233.4 ± 23.9 s; 95% limits of agreement (LoA): −5.5, 15.3]. The Concept 2 SkiErg™ time-trial had a coefficient of variation (CV) of 1.6% and the standard error of measurement was 3.8 s. When compared to the on-snow time-trial, the Concept 2 SkiErg™ time-trial demonstrated a mean bias of 20.7 s (95% LoA; 11.6, 29.8) and the concordance correlation coefficient was 0.72.ConclusionThe Concept 2 SkiErg™ demonstrated excellent single-trial reliability. However, there was significant proportional bias in the Concept 2 SkiErg™ relative to the on-snow test and agreement between the two was relatively poor. Research using a larger sample and different trial durations is required to further validate the Concept 2 SkiErg™ for cross-country skiing performance testing.